The Influence of Work Motivation and Work Discipline on Employee Performance at Public Health Centers in Surabaya with Job Satisfaction as a Mediating Variable - Rahmawati, Dania; Burhanudin, Burhanudin; Tjahjani Prawitowati, Tjahjani (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to analyze the effect of work motivation and work discipline on employee performance at Public Health Centers (Puskesmas) in Surabaya, with job satisfaction as a mediating variable. A quantitative approach was used through the distribution of questionnaires to Puskesmas employees. The results showed that work motivation and discipline have a positive and significant effect on job satisfaction and employee performance. Furthermore, job satisfaction mediates the effect of motivation and discipline on performance. These findings emphasize the importance of internal employee factors in improving the quality of public health services